Connexin 43 contributes to temporomandibular joint inflammation induced-hypernociception via sodium channel 1.7 in trigeminal ganglion. (10th August 2019) - Jin, Yi-Zhou; Zhang, Peng; Hao, Ting; Wang, Lu-Ming; Guo, Mu-Di; Gan, Ye-Hua
Highlights: TMJ inflammation induces morphological alterations of SGCs in TG. TMJ inflammation results in increased expression of Cx43 in SGCs. Cx43 blockers attenuate TMJ inflammation-induced hypernociception via Nav1.7. Abstract: We previously demonstrated that sodium channel 1.7 (Nav1.7) in trigeminal ganglion (TG) was a critical factor in temporomandibular joint (TMJ) inflammation-induced hypernociception, but the mechanism underlying inflammation-induced upregulation of Nav1.7 remained unclear. Glial-neuron interaction plays a critical role in pain process and connexin 43 (Cx43), a gap junction protein expressed in satellite glial cells (SGCs) has been shown to play an important role in several pain models. In the present study, we investigate the role of Cx43 in TMJ inflammation-induced hypernociception and its possible impact on neuronal Nav1.7. We induced TMJ inflammation in rats by injecting complete Freund's adjuvant (CFA) into TMJ and observed a decrease in head withdraw threshold after 24 h. Electron microscopy showed morphological alterations of SGCs in TMJ-inflamed rats. The expression of Cx43, glial fibrillary acidic protein (GFAP), and Nav1.7 increased greatly compared with controls. In addition, pretreatment with Cx43 blockers in TMJ-inflamed rats could alleviate mechanical hypernociception, inhibit SGCs activation and IL-1βrelease, and thus block the upregulation of Nav1.7. These findings indicate that the propagation of SGCs activation via Cx43 plays a critical role in Nav1.7-involved mechanical hypernociception induced by TMJ inflammation.